Evaluation of Arbuscular Mycorrhiza Fungi Species for Their Efficiency Towards Nutrient Acquisition in Rhizospheric Soil of Maize - Beura, Kasturikasen; Singh, Mahendra; Pradhan, Amit Kumar; Rakshit, Rajiv; Lal, Manohar (International Journal of Bio-resource and Stress Management, 2023)
An investigation was carried out to evaluate the response of selected species of mycorrhizae for nutrient acquisition and phosphorus uptake by maize in an alluvial soils of Bihar. The study was undertaken during 2013 wet season (July to December) in a net-house at Bihar Agricultural University. Six treatments along with a control treatment were maintained with three replications for the experiment. Five species of AM fungi collected from TERI (The Energy and Resources Institute) along with a local species from long term litchi orchard (Muzaffarpur), were evaluated on the basis of nutrient acquisition in the soil rhizospeheric region for maize crop. The results obtained clearly show that of all the species of mycorrhizae taken under consideration, Glomus mosseae was found to perform better in terms of nutrient acquisition and uptake of P to plant. The maximum P concentration (7.65 mg kg-1), organic carbon (0.60%) and Zn Concentration (6.48 mg kg-1) and P uptake (was also found with the application of G. mosseae. The AM (Arbuscular Mycorrhiza) species significantly increased the released of P and micronutrients in the soil of rhizospheric region of maize plant. The beneficial effect was more pronounced for the treatment in case of Glomus mossae among all the other species used. This may be due to the higher solubilization power of Glomus mossae forsoil nutrientsthan other species.